2021
DOI: 10.1080/23320885.2021.2016057
|View full text |Cite
|
Sign up to set email alerts
|

Orf virus infection of the hand in a Scottish sheep farmer. A case report to increase awareness to avoid misdiagnosis

Abstract: Awareness of infections which are transmitted between animals and humans have been given prominence following the (COVID-19) pandemic. The Orf infection in humans is rare. Recognition of Orf lesions avoids misdiagnosing and incorrect treatment. We present a case of a Scottish-farmer with pain and discomfort from a lesion on her finger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…For the transmission of ORFV to humans, the most widely reported route is direct contact with diseased animals ( Nougairede et al, 2013 ; Kitchen et al, 2014 ; Zhang et al, 2014 ; Hasheminasab et al, 2016 ; Lopez-Cedeno et al, 2018 ; Andreani et al, 2019 ; Qiu and Yanes, 2021 ; Khan et al, 2022 ). However, several important clues doses implicate the presence of other transmission routes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the transmission of ORFV to humans, the most widely reported route is direct contact with diseased animals ( Nougairede et al, 2013 ; Kitchen et al, 2014 ; Zhang et al, 2014 ; Hasheminasab et al, 2016 ; Lopez-Cedeno et al, 2018 ; Andreani et al, 2019 ; Qiu and Yanes, 2021 ; Khan et al, 2022 ). However, several important clues doses implicate the presence of other transmission routes.…”
Section: Discussionmentioning
confidence: 99%
“…However, several important clues doses implicate the presence of other transmission routes. For example, Khan et al (2022) reported a case of Orf in a Scottish Sheep farmer with pain and discomfort. She had not seen any Orf lesions around the mouths of her sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orf primarily affects domestic small ruminants, such as sheep and goats, and occasionally wild small ruminants like deer and camels (5,6). The disease can be transmitted to humans either through direct contact with infected animals or by consuming contaminated animal products (7)(8)(9). The case of human-to-human transmission of Orf has also been reported recently (10).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of human-to-human transmission of orf are rare but do occur (Turk et al, 2014;Rajkomar et al, 2016;Bouscarat and Descamps, 2017). Clinical manifestation of human orf usually begins with small papules, which then progress into severe pustular dermatitis lesions, most commonly on the hands and arms (Khan et al, 2021;Qiu and Yanes, 2021). Although orf in humans is a benign and self-limiting disease, it can become complicated in patients with compromised immune systems (Lederman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%